Effort Gains in Occupational Teams – The Effects of Social Competition and Social Indispensability - Hertel, Guido; Nohe, Christoph; Wessolowski, Katrin; Meltz, Oliver; Pape, Justina C.; Fink, Jonas; Hüffmeier, Joachim (Frontiers in Psychology, 2018)
Laboratory research has demonstrated social competition and social indispensability as potential triggers of effort gains in teams as compared to working alone. However, it is unclear whether such effects are also relevant for existing occupational teams, collaborating for longer time intervals and achieving meaningful outcomes. We assumed that social indispensability effects are prevalent and stable in occupational teams, whereas social competition effects should mainly be effective in the beginning of teamwork and fade out over time. Hypotheses were confirmed in two studies using within-subjects designs with employees recruited via an online panel (Study 1, N = 137) and in software development companies (Study 2, N = 70). By means of the Event Reconstruction Method, participants re-experienced specific events from past working days (three events working alone, three teamwork events), and rated their effort separately for these events. In both studies, multilevel analyses revealed significant effort gains in teams when event-specific social indispensability was high. These effects were mediated by positive mood and perceived task meaningfulness, and additionally qualified by employees’ preference for teamwork. In contrast, motivating effects due to event-specific social competition were only observed for teams with short as compared to long team tenure in Study 2.